Sightings limited to Iowa list from 3/1/93 to 5/28/93, Jim and Joyce Durbin - Durbin, James O.et al; Durbin, Joyceet al (1993)
An annotated list of birds sighted by Jim and Joyce Durbin. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1993. Plustek - flatbed